Extraordinarily Ordinary. Working in the Social Economy - Amin, Ash (Journal of Public Governance, 2009)
It is with ever-increasing attention that political actors worldwide watch social economy – the segment of the economy focussed on meeting social needs usually by third-sector organizations – for the purpose of strengthening and development of various social policy instruments. Once considered an insignificant complement to the free market, social economy is nowadays perceived as a rightful member of the market economy that can develop thanks to efforts of individuals and organizations united in their efforts geared towards the accomplishment of the idea of ethical entrepreneurship. It is assumed that in order to be able to meet new challenges, the capitalism of the future may need the dynamics of social economy in the process of creation of new markets and the functions customarily associatedwith the welfare state.Mainstream research into social economy focuses on analysing its constitutive features and the relationships that hold among its postulated ethical values and the market. Issues concerning the social determinants of its development, including the motivations and professional career paths of individuals involved in the operation of social economy enterprises, have attracted marginal treatment from researchers.We only have a very general knowledge of the motives that induce social actors to be involved in activities in the area of social economy and the advantages that accrue to them. Results of analyses show only some general premises, such as solidarity and reciprocity. The aim of this study is to fill this gap by describing the experience of social businessmen, workers and volunteers based on a case study involving the city of Bristol.